Care-associated adverse events related to the use of laser in urological interventions: the French experience - Abdessater, Maher; Panthier, Frédéric; Michel, Philippe; Avrillon, Vanessa; Pogu, Bertrand; Bart, Stéphane (Frontiers in Urology, 2025)
IntroductionThe use of laser in urology is increasing, especially in renal stones and benign prostatic hypertrophy. Despite the interest in this technology on improving surgical management, several adverse events may result. This work collates French reports of care-associated adverse events (CAEs) resulting from lasers used in urological interventions.Materials and methodsThis is a collection of CAEs between May 2016 and December 2023 declared by urologists involved in accreditation throughout France. These CAEs were classified according to five levels of severity. They have been described and classified according to the ALARM protocol. The statistics were mainly descriptive. Fisher’s exact test and Student’s t-test were used via the software R.ResultsBetween May 2016 and December 2023, between the 1,376 declared events, 149 laser-related CAEs were reported in urological interventions. Five CAEs (3.4%) were classified as grade 3, and six CAEs (4%) were classified as grade 4. All the other CAEs were between grades 1 and 2 with negligible consequences. The immediate reported causes of laser AEs were the clinical complexity of the case (7.38%), the technical gesture (14.1%), patient information (24.83%), material (38.25%), and medications (15.43%). Incidents caused by problems in material seem to be more frequent in younger patients (p < 0.001), healthier patients (ASA 1) (p = 0.003), risky situations (p < 0.001), and laser procedures (p < 0.001).ConclusionIn France, 7.4% of CAEs related to the use of laser in urological surgery are of major to critical severity. Training teams on the use of laser generators and providing feedback on functional results and related specific morbidity seem necessary to guarantee the proper use of these technologies and the safety of staff and patients.